Mission of serving the poor : SEWA rural - Pingali, Viswanath, (SAGE Business cases., 2024)
The case looks at the challenges faced by SEWA Rural, a non-profit organisation located in Jhagadia, Gujarat, India. Started in 1980, the trust has been instrumental in establishing a robust healthcare system in Jhagadia, especially in the areas of child and maternal health. Along with a primary care hospital, the trust is also involved in community health, child care and education, women and girl child empowerment, and vocational education. The trust, currently, is considering its future course of action and its vision is for year 2030. The three protagonists: Dr. Shrey Desai, Dr. Gayatri Desai and Dr. Dhiren Modi, were entrusted with coming up with a plan for the same.